El mercado de los Criptoactivos: ¿hasta dónde llega la responsabilidad de los Exchanges? - Castelli, Leandro M. (2024)
The digital asset market has experienced rapid global growth in the past years driven technological advances, which occurred within a regulatory framework designed for a different type of assets and businesses. Platforms that facilitate the exchange and storage of crypto assets, known as “Exchanges”, are exposed to the risks of internet use and those specific of the crypto-asset environment. In this article, we provide certain guidelines for a better understanding of the role of Exchanges and the limits of their responsibility.Starting from this premise, in the article, we (i) analyze the legal nature of crypto assets to understand how they should be treated. We delve into topics such as the determination of their value, inherent risks, trading, and the protocols that govern them. (ii) We also address the Exchange’s responsibility for the various risks posed by crypto assets, including contract formation, typical clauses, and protective regimes. (iii) Lastly, we explore the difference between a consumer and an investor, dissecting the characteristics of the operations each engages in and the applicable legal frameworks.